Comparative study on protein expression of chicken heart between commercial broilers and indigenous chicken - Soffian, Sharmeen Nellisa; Abu Hassan, Muhamad Shafiq; Muhamad Bunnori, Noraslinda (2014)
Broiler chicken are produced by modern integrated poultry raising facilities and been chosen by the farmers due to their high feed-meat conversion ratio ability. This type of chicken is raised in condition which involves antibiotic feed in order to make the chicken gain weight faster and also healthier. Farmers have focused to maximize the production of meat in the shortest time to supply the demand of chicken in the market. However, they may have health issues caused by the fast growth, including sudden death syndrome, metabolic problems such as ascites, and leg problems such as lameness. To analyse the protein expression of chicken liver tissue between antibiotic and non-antibiotic treated chicken through second dimension gel electrophoresis. Protein extraction was carried out according to Zaman et. al. without any modification. The protein concentration of each sample was assayed using Bradford Assay, a Coomassie dye-binding method. A standard curve was generated with serial dilution of bovine serum albumin (BSA) to get the protein concentration of the sample. The protein sample for each replicates was prepared for in-gel rehydration with rehydration buffer such that the concentration of protein applied to each IPG (Immobilized pH Gradient) strip was 120 µg in rehydration buffer and with a total volume of 125 µL. Strip were carefully placed into the SDS-PAGE gel slightly above the well with the gel side facing out and such that the + 3-10 pH sign was on the left side. he gel was viewed using GS-800™ Calibrated Densitometer (Bio-Rad) using Quantity One 1D Analysis software version 4.5 and PDQuest 2D Analysis software (Bio-Rad). Spots of interest were identified using ExPASy SWISS-2DPAGE database (world-2dpage.expasy.org/swiss-2dpage/) as reference. The mean value of protein concentrations in broilers chicken and indigenous chicken heart tissues are 10.43 μg/μL and 11.06 μg/μL respectively. Three spots were identified which shows differential protein expression. First spot is near pH 4.0 with Mw 50-75 kDa which highly expressed in broilers compared to indigenous chicken; second spot is near pH 7.0 with Mw 10-15 kDa, which have a higher spot intensity in indigenous chicken compared to broiler; and third spot is at pH 6.0, Mw 25-37 kDa which expressed in broiler but absent in indigenous chicken. The possible candidates for protein spots which belong to spot i, ii and ii which might represent alpha-1-antitrypsin, myoglobin, and heat shock protein 27 (HSP27) respectively after comparing with HEART-2DPAGE database (http://userpage.chemie.fu-berlin.de/~pleiss/protein_all.html).The Alpha-1-antitrypsin (AAT) is a protease inhibitor that possesses anti-inflammatory and tissue-protective properties. AAT inhibits caspase-1 activity in the condition of inadequate blood supply (ischemia) in myocardium that will help the preservation of viable myocardium. The highly expressed AAT in commercial broilers might appear as a mechanism to overcome or reduce the common heart failure among broilers. Based on the result of 2D gel, the broiler’s heart contains lower concentration of myoglobin compared with indigenous chicken’s heart which is might be the key factor of common case of heart failure among broilers due to lack of oxygen supply by the red blood cells to the heart tissue. Heat Shock Protein (HSP) is expressed in response with the environmental stresses such as heat shock, hypoxia and water deprivation. The functions of the expression of HSP in cells are to adapt to environmental changes and survive from different type of injuries. From the gel, the HSP27 protein was expressed in broilers’ heart while not in the indigenous chicken’s heart. The expression of HSP27 protein in broiler gives signals that the broiler’s chicken heart is under the stress condition, which was assumed to be hypoxia. Thus, the expression of HSP27 in broiler’s heart might aid the cells to survive in the hypoxic condition.